2017
DOI: 10.1371/journal.pntd.0005651
|View full text |Cite
|
Sign up to set email alerts
|

Community effectiveness of pyriproxyfen as a dengue vector control method: A systematic review

Abstract: BackgroundVector control is the only widely utilised method for primary prevention and control of dengue. The use of pyriproxyfen may be promising, and autodissemination approach may reach hard to reach breeding places. It offers a unique mode of action (juvenile hormone mimic) and as an additional tool for the management of insecticide resistance among Aedes vectors. However, evidence of efficacy and community effectiveness (CE) remains limited.ObjectiveThe aim of this systematic review is to compile and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 31 publications
1
49
1
1
Order By: Relevance
“…In our study, the diluted 0.01% PPF commercial product could be directly applied for residual spraying without any pretreatment. On the other hand, the concentration of PPF product used in previous autodissemination studies varied from 0.5-10% and could result in larval/pupal mortality of the dengue vector of more than 60% [9,11,21,24,30]. The concentration of PPF product used in our study (0.01%) was relatively low compared to that in other studies, and the result showed that the mean EI% was 37% one month post-spraying.…”
Section: Discussioncontrasting
confidence: 65%
“…In our study, the diluted 0.01% PPF commercial product could be directly applied for residual spraying without any pretreatment. On the other hand, the concentration of PPF product used in previous autodissemination studies varied from 0.5-10% and could result in larval/pupal mortality of the dengue vector of more than 60% [9,11,21,24,30]. The concentration of PPF product used in our study (0.01%) was relatively low compared to that in other studies, and the result showed that the mean EI% was 37% one month post-spraying.…”
Section: Discussioncontrasting
confidence: 65%
“…Novel vector control methods include lethal ovitraps [ 18 ], insect growth regulators ( e . g ., pyroproxyfen) [ 19 ], Wolbachia infections [ 20 ], and genetically-modified sterile mosquitoes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…aegypti [16], and may decrease the risk of exposure to infected mosquitoes in households with DENV infections [17]. Novel vector control methods include lethal ovitraps [18], insect growth regulators (e.g., pyroproxyfen) [19], Wolbachia infections [20], and introduction of genetically-modified sterile mosquitoes into the population [21].…”
Section: Introductionmentioning
confidence: 99%